Effects of temperature and pressure on volatile compounds of black cumin seeds (Nigella sativa L.) oil extracted by supercritical carbon dioxide - Sakdasri, Winatta; Sakulkittiyut, Buntita; Ngamprasertsith, Somkiat; Supang, Wirasinee; Sawangkeaw, Ruengwit (My University, 2025)
This study investigated the effects of temperature and pressure on the yield and volatile compound contents of black cumin seed oil (BCO) extracted from black cumin seeds using supercritical carbon dioxide (SCCO2). The solubility of BCO in SCCO2 increased 2.5-fold as the pressure increased by 10 MPa. Major volatile compounds in BCO were identified using a static headspace gas chromatography–mass spectrometry (SH–GC–MS). Evidence indicated the main volatile components in SCCO2-extracted BCO to be hexanal, p-cymene, and thymoquinone. BCO extracted from China-cultivated black cumin seed contained similar amounts of p-cymene and thymoquinone. This black cumin seed is classified as the cymene/thymoquinone chemotype and is also found in Indian, Iranian, and Algerian black cumin seeds. Thymoquinone contents in BCO were more sensitive to the extraction temperature than hexanal and p-cymene contents. The maximum oil yield of 36.28 ± 1.38 wt%, with approximately 2.0 mg of thymoquinone per milliliter of oil, was obtained at extraction temperatures of 50°C and pressures of 30 MPa. A SH–GC–MS could detect small molecules in black cumin seed oil such as hexanal. The results of this work reveal that temperature has more impact on the selectivity of volatile compounds than pressure in supercritical carbon dioxide extraction.
Keywords: black cumin; Nigella sativa L. seed oil; seed oil; supercritical carbon dioxide; thymoquinone